Method and approach Mapping for Agri-food Supply Chain Risk Management: A literature review - Winnie Septiani; Marimin Marimin; Yeni Herdiyeni; Liesbetini Haditjaroko (International Journal of Supply Chain Management, 2016)
One of the agri-food characteristics is perishable product which made it has a higher chance damage risk from the farmer to the consumer. While issues around food security and associated risks are extremely important. Some methods or approaches have been used to identify and assess risks that occur in agri-food supply chain. The purpose of this paper was to identify the development of methods or approaches used to identify and assess the risks that occured in the agri-food supply chain. The articles search was undertaken through articles search on selected relevant journals of supply chain risk management for agri-food published from 2004 until 2014. A total of 77 randomly selected journal articles had been analyzed. These mapping were arranged in systematic stages, started from searches related supply chain risk management for agrifood. Furthermore, the articles identified and classified the methods or approaches for each stage of supply chain risk management, and were divided into three main stages: risk identification, risk assessment and risk mitigation. The last, the articles of risk identification are categorized into three groups : qualitative, semi-quantitative and qualitative.The mapping results showed that risk assessment supply chain for agri-food was much related to microbiology risk assessment. It related to the characteristics of agri-food products. Standard models used for risk assessment in supply chain for agri-food were based on integration of statistical analysis and simulation. The other techniques used included intelligent technique, optimization models and multi-criteria decision analysis. The literature on supply chain risk management for agri-food is so vast, complex and difficult to understand that a mapping of method and approach is needed and much value for the research community. Keywords :supply chain risk, risk identification, risk assessment, risk mitigation, agri-food